The Mediating Role Of Organizational Culture In The Link Between Leadership Style And Employee Performance - Andi Amang; Ferdy Leuhery; M. Syukur Dwiriansyah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Leadership style plays a crucial role in shaping employee performance, particularly when mediated by the organizational culture that defines shared values, behaviors, and workplace norms. This study investigates how different leadership styles transformational, visionary, and participative affect employee performance through the mediating mechanism of organizational culture within modern management contexts. Using a mixed-method approach that combines quantitative survey analysis and qualitative interviews, data were collected from employees in education, service, and technology sectors to assess leadership effectiveness, cultural alignment, and performance outcomes. The findings indicate that transformational and visionary leadership styles foster a positive organizational culture characterized by collaboration, innovation, and trust, which significantly enhances employee engagement and productivity. Conversely, environments with weak or inconsistent cultural support show diminished leadership impact on performance. This study contributes to the understanding of how leaders can cultivate adaptive and value-driven cultures that sustain performance excellence and organizational sustainability.